2016
DOI: 10.3892/ol.2016.5448
|View full text |Cite
|
Sign up to set email alerts
|

Host knockout of E-prostanoid 2 receptors reduces tumor growth and causes major alterations of gene expression in prostaglandin E2-producing tumors

Abstract: Abstract. Prostaglandin E 2 (PGE 2 ) is elevated in a variety of malignant tumors and has been shown to affect several hallmarks of cancer. Accordingly, the PGE 2 receptor, E-prostanoid 2 (EP2), has been reported to be associated with patient survival and reduced tumor growth in EP2-knockout mice. Thus, the aim of the present study was to screen for major gene expression alterations in tumor tissue growing in EP2-knockout mice. EP2-knockout mice were bred and implanted with EP2 receptor-expressing and PGE 2 -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
5
12
0
Order By: Relevance
“…Prostaglandin E2 (PGE2) receptor 2 subtype (EP2) is a G protein-coupled plasma membrane receptor for PGE2, which acts through numerous signaling pathways to regulate various physiological functions, including tumor occurrence, invasion and metastasis, angiogenesis, chronic inflammation, tumor immunity and cell apoptosis (1). Recently, various studies have focused on identifying the specific EP2 receptors and signaling pathways that regulate the pleiotropic activities of the cyclooxygenase-2 (cOX-2)/PGE2/EP2 pathway (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E2 (PGE2) receptor 2 subtype (EP2) is a G protein-coupled plasma membrane receptor for PGE2, which acts through numerous signaling pathways to regulate various physiological functions, including tumor occurrence, invasion and metastasis, angiogenesis, chronic inflammation, tumor immunity and cell apoptosis (1). Recently, various studies have focused on identifying the specific EP2 receptors and signaling pathways that regulate the pleiotropic activities of the cyclooxygenase-2 (cOX-2)/PGE2/EP2 pathway (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years, cOX-2 and its prostaglandin products have attracted increasing attention due to their important roles in the progression of tumors of the lung, head and neck, prostate, colon, ovary, chest and liver (2,(6)(7)(8). However, inhibition of COX-2 using non-steroidal anti-inflammatory drugs (NSAIDs) and specific COX-2 inhibitors is associated with various side effects, including gastric ulcers and myocardial infarction (9), which have limited the use of these drugs (10).…”
Section: Introductionmentioning
confidence: 99%
“…EP2 is mostly responsible for the protumorigenic effects of PGE 2 . EP2 knockout mice showed reduced tumorigenesis in a carcinogen-induced skin cancer model, while EP2 overexpressing transgenic mice exhibited increased numbers of tumors when compared with wild-type mice ( Sung et al ., 2006 ; Asting et al ., 2017 ). Moreover, the PGE 2 -EP2/EP4 signaling axis can induce MMP-9 expression as well as its activation, resulting in the invasion and migration of human endometrial epithelial and stromal cells ( Lee et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth is inhibited in EP2-knockout mice compared with wild-type mice 37-39 . Asting et al showed that tumor growth, systemic inflammation and the expression of interleukin-6 are reduced in www.nature.com/scientificreports www.nature.com/scientificreports/ EP2-knockout tumor-bearing mice 40 . Tian et al found that EP2 methylation is associated with a better prognosis of non-small cell lung cancer, and EP2 methylation is present with greater frequency in tumors with epidermal growth factor receptor (EGFR) mutation than in non-EGFR mutated tumors 41 .…”
Section: Discussionmentioning
confidence: 99%